A Clinical Review of COVID-19 Associated Myocarditis - Sakibuzzaman, Md; Fariza, Tasnuva Tarannum; Rahman, S M Tajdit; Haque, Mahaim Maksumul; Moosa, Syed Ahmad (Archives of Clinical and Biomedical Research, 2020)
The Coronavirus 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2(SARS COV-2) which can cause multi-organ dysfunction with noteworthy ramifications for patients' cardiovascular consideration. Complications like myocarditis, myocardial injury, acute-onset heart failure, acute coronary syndrome, arrhythmia have been reported. However, a limited number of case reports, retrospective studies, and impairing factors, including the lack of proper diagnostic modalities for COVID-19 associated myocarditis, have made the exact incidence of myocarditis from COVID-19 unclear. In this paper, we have analyzed peer-reviewed articles to highlight COVID-19 myocarditis and outline the associated risk factors, pathophysiology, symptoms, diagnosis, and management of such patients. This is to ensure rapid triage, so their treatment is not compromised and thereby averting fatal complications from it.